Production model for the reduction of order delivery time in a peruvian metalworking company based on the six sigma dmaic methodology - Espinoza-Cuadros, Anelit (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.